1999
DOI: 10.1038/sj.cr.7290006
|View full text |Cite
|
Sign up to set email alerts
|

Tropomyosin is localized in the nuclear matrix and chromosome scaffold of physarum polycephalum

Abstract: The nuclei and chromosomes were isolated from plasmodia of Physarum polycephalum. The nuclear matrix and chromosome scaffold were obtained after the DNA and most of the proteins were extracted with DNase I and 2 M NaCl. SDS-PAGE analyses revealed that the nuclear matrix and chromosome scaffold contained a 37 kD polypeptide which is equivalent to tropomyosin in molecular weight. Immunofluorescence observations upon slide preparations labeled with anti-tropomyosin antibody showed that the nuclear matrix and chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Other cytoskeletal proteins have also been found in nuclei (32,33,43,44). Zhao et al (45) recently showed that ␤-actin is a subunit of the SWI/SNI-like BAF (Brg-associated factor) complex in the nucleus and is involved in chromatin remodeling in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other cytoskeletal proteins have also been found in nuclei (32,33,43,44). Zhao et al (45) recently showed that ␤-actin is a subunit of the SWI/SNI-like BAF (Brg-associated factor) complex in the nucleus and is involved in chromatin remodeling in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…They possess some important biological activities, such as the ability to inhibit mammalian cell division as well as protease, antibiosis, and antitumor activities (Espada et al, 1997). Cytochalasin B (CB) can pass through the cell membrane and bind to F-actin, which inhibits the superposition of G-actins and promotes cytoskeleton depolymerization (Zeng et al, 1997). The cytoskeleton affects cell morphology, cytoplasm flow, chromosome polymerization, and the location and directional movement of nuclei.…”
Section: Introductionmentioning
confidence: 99%